A Qualitative Exploration on Psychological Stressors and Coping Mechanisms in Medical Laboratory Personnel - Zhu, Kui; Chen, Zijian (Pacific International Journal, 2024)
Healthcare professionals, particularly those working in high-stress environments like hospitals, are frequently exposed to significant psychological challenges. This study explores the psychological stressors and coping mechanisms of medical laboratory personnel at the People's Hospital of Keyouqianqi, Inner Mongolia, China. Using a qualitative research design, data was collected through semi-structured interviews with 10 participants, focusing on their experiences of stress and the strategies they use to manage it. The findings reveal that the most significant stressors include high workloads, time pressure, the responsibility for diagnostic accuracy, and interpersonal conflicts within the workplace. Additionally, personal and social stressors, such as balancing work with family responsibilities, further compounded their stress levels. Participants employed a variety of coping mechanisms, both problem-focused and emotion-focused, with effective strategies including building strong professional relationships, engaging in physical activities, and practicing mindfulness. However, some participants resorted to ineffective coping strategies, such as avoidance behaviors and unhealthy habits, which often exacerbated their stress. This study highlights the complex interplay between individual coping strategies and the cultural and institutional context in which these professionals operate. The findings have important implications for practice and policy, offering insights into how healthcare institutions can better support the mental health and well-being of their staff.